Treatment characteristics and outcomes of pure acinar cell carcinoma of the pancreas: a multicentric European study on radically resected patients - Bellotti, Ruben; Paiella, Salvatore; Primavesi, Florian; Jäger, Carsten; Demir, Ihsan E.; Casciani, Fabio; Kornprat, Peter; Wagner, Doris; Rösch, Christiane S.; Butturini, Giovanni; Giardino, Alessandro; Goretzky, Peter E.; et al. (HPB, 2023)
Background - Acinar cell carcinomas (ACC) belong to the exocrine pancreatic malignancies. Due to their rarity, there is no consensus regarding treatment strategies for resectable ACC. - Methods - This is a retrospective multicentric study of radically resected pure pancreatic ACC. Primary endpoints were overall survival (OS) and disease-free survival (DFS). Further endpoints were oncologic outcomes related to tumor stage and therapeutic protocols. - Results - 59 patients (44 men) with a median age of 64 years were included. The median tumor size was 45.0 mm. 61.0% were pT3 (n = 36), nodal positivity rate was 37.3% (n = 22), and synchronous distant metastases were present in 10.1% of the patients (n = 6). 5-Years OS was 60.9% and median DFS 30 months. 24 out of 31 recurred systemically (n = 18 only systemic, n = 6 local and systemic). Regarding TNM-staging, only the N2-stage negatively influenced OS and DFS (p = 0.004, p = 0.001). Adjuvant treatment protocols (performed in 62.7%) did neither improve OS (p = 0.542) nor DFS (p = 0.159). In 9 cases, radical resection was achieved following neoadjuvant therapy. - Discussion - Radical surgery is currently the mainstay for resectable ACC, even for limited metastatic disease. Novel (neo)adjuvant treatment strategies are needed, since current systemic therapies do not result in a clear survival benefit in the perioperative setting.
Online verfügbar 27 July 2023, Version des Artikels 21 October 2023
Gesehen am 17.05.2024